1986
DOI: 10.1007/bf00691047
|View full text |Cite
|
Sign up to set email alerts
|

How do food passage rate and assimilation differ between herbivorous lizards and nonruminant mammals?

Abstract: What digestive adaptations permit herbivorous nonruminant mammals to sustain much higher metabolic rates than herbivorous lizards, despite gross similarity in digestive anatomy and physiology? We approached this question by comparing four herbivorous species eating the same diet of alfalfa pellets: two lizards (chuckwalla and desert iugana) and two mammals (desert woodrat and laboratory mouse). The mammals had longer small and large intestines, greater intestinal surface area, much higher (by an order of magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 29 publications
6
62
0
Order By: Relevance
“…In our study, lizards fed the plant-rich diet exhibited a dry matter digestibility of 63%. This is similar to measurements of dry matter digestibility in two species of herbivorous lizards on high-fiber diets: 47-66% in the chuckwalla (Sauromalus obesus; Karasov et al, 1986;Ruppert, 1980) and 45-66% in the desert iguana (Dipsosaurus dorsalis; Harlow et al, 1976;Karasov et al, 1986). Further, L. ruibali digested 24% of total fiber, with no differences between diet treatments.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In our study, lizards fed the plant-rich diet exhibited a dry matter digestibility of 63%. This is similar to measurements of dry matter digestibility in two species of herbivorous lizards on high-fiber diets: 47-66% in the chuckwalla (Sauromalus obesus; Karasov et al, 1986;Ruppert, 1980) and 45-66% in the desert iguana (Dipsosaurus dorsalis; Harlow et al, 1976;Karasov et al, 1986). Further, L. ruibali digested 24% of total fiber, with no differences between diet treatments.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, lizards might be limited in their ability to feed on lownitrogen foods and maintain nitrogen balance. Additionally, low digestive efficiency may limit the ability of lizards to feed on highfiber food (Karasov et al, 1986;Ruppert, 1980). Last, it has also been suggested that limitations in the ability for the gut microbial communities of lizards to aid in digestion may constrain the evolution of herbivory (Karasov et al, 1986;Sokol, 1967;Szarski, 1962), though some herbivorous lizards have well-developed associations with gut microbes (Mackie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This principle suggests that 42 larger species can feed on diets of lesser quality (i.e., higher fibre content). The proposed 43 mechanistic background of this concept is the fact that whereas metabolic requirements and 44 hence food intake scales to body mass 0.75 , gut capacity scales linearly to body mass; in other 45 words, the amount of food ingested decreases per unit gut capacity, which should in theory 46 lead to an increase in digesta retention time with increasing body mass (Parra 1978 Because of the perceived relevance of digesta retention, numerous studies have 54 investigated this parameter, often in conjunction with digestibility measurements (reviewed in 55 Clauss et al 2007a been evoked for comparisons between chewing and non-chewing dinosaurs (Farlow 1987; 75 Sander and Clauss 2008), between reptiles and mammals (Karasov et al 1986), between 76 different large mammalian hindgut fermenters (Clauss et al 2005), between ruminant and 77 non-ruminant foregut fermenters (Schwarm et al 2009), or between the sexes of a dimorphic 78 ruminant species (Gross et al 1995). However, a statistical demonstration of such a 79 compensating effect across species has not been presented so far, most likely because data on 80 digestibility, digesta retention and digesta particle size was not available for a suffficiently 81 large dataset (Schwarm et al 2009).…”
Section: Introduction 40mentioning
confidence: 99%
“…Therefore, particle size reduction is often considered the key digestive difference between ecto-and endotherms (Karasov et al 1986;Farlow 1987;Fritz et al 2010) that allows endotherms to rely on shorter digesta retention times without losing digestive efficiency (Franz et al 2011), and hence facilitate the high level of food intake necessary to meet their increased metabolic requirements.…”
Section: Discussionmentioning
confidence: 99%